Mitä väliä on historialla? - Miettinen, Tiina; Toivo Maria, Raisa (Tampere University Press, 2016)
Mitä väliä on historialla ("What good is history?") is edited by Dr. Tiina Miettinen and Dr. Raisa Maria Toivo. Can history be useful and if so, what is it useful for? This book explores the impact of history and historical research. It gives a general introduction and various case studies - together with a piece of fiction - on how different parts of society can benefit, or have used, the study of history.